Smart - MiLan: Administrative Systems and Services at the Faculty of Communication and Information Technology: Smart - MiLan: Administrative Systems and Services at the Faculty of Communication and Information Technology - Ahmad Fahreza; Septi Andryana; Ratih Titi Komalasari (Institute of Computer Science (IOCS), 2020)
Mastery of information technology in this era has become a necessity. Information technology becomes a tool in communicating and adding knowledge in this globalization and information age era. More specifically for institutions, including the need to expedite the work of service administration, one example is administrative administration in filing letters. The speed of data processing and delivery of information has a very important role for Administration. Processing large amounts of data requires a tool that has a high level of calculation speed and data delivery. With the application of this information system can help the FTKI in managing incoming and outgoing mail and assist in archiving and reporting.